Gambaran Pengetahuan Perawat Tentang Mutu Pelayanan Keperawatan Di Rumah Sakit PKU Muhammadiyah Surakarta - Hayeeduereh, Waeameenoh; , Supratman, SKM., M.Kes., Ph.D (2016)
Quality and service are the means to achieve patient satisfaction. Therefore, it provides high quality and excellent service is a must. The purpose of this study is to describe the nurse's knowledge about the quality of health services in hospitals PKU Muhammadiyah Surakarta. This type of quantitative research using simple criptive. The sample were nurses at the Hospital of PKU Muhammadiyah Surakarta. With samplesize 77 nurses. The research instrument used a questionnaire quality of nursing service. Data analysis is performed using univariate against each outcome variable of the study. The survey results revealed Characteristics of respondents by age shows the distribution of the highest is 22-30 years as many as 46 nurses (60%), the next 31-40 years as many as 25 nurses (32%) and 41-50 years as many as 6 nurses (8%). Characteristics of respondents by sex showed the highest distribution are women as much as 52 nurses (67%) and men by 25 nurses (33%). Characteristics of respondents according to education shows the highest distribution is D-III Health as many as 71 nurses (92%) and the remaining S1 Nursing as 6 nurses (8%). Characteristics of respondents by length of employment showed the highest distribution is 1-5 years as many as 47 nurses (615), the next 6-10 years as many as 17 nurses (22%), and more than 10 years as many as 13 nurses (17%). the nurse's knowledge of the quality of nursing care hospitals showed the highest distribution is high as many as 65 nurses (84%) and were as much as 12 nurses (16%). Actually, it is proper respondents who are nurses have sufficient knowledge and competency of nursing. Distribution of working time nurses showed mostly between 1-5 years, but most of them have worked between 2-3 years.